2009
DOI: 10.1161/atvbaha.109.188656
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Protects Against Myocardial Ischemia/ Reperfusion Injury via Inhibition of Apoptosis and Inflammation

Abstract: Objective-In spite of major advances in reperfusion therapy for patients presenting with acute coronary syndrome, long-term morbidity is still substantial. A limitation of initial treatment of myocardial ischemia is the lack of prevention of ischemia/reperfusion (I/R) injury. Activated protein C (APC), a crucial mediator in the coagulation process, plays a prominent role in the crosstalk between coagulation and inflammation and provides cytoprotective effects via inhibition of apoptosis and inflammation in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 29 publications
2
63
1
Order By: Relevance
“…Inhibition of factor Xa has been shown to reduce inflammation in a model of acute myocardial I/R injury [21]. This protective effect has been associated with phosphorylation of ERK1/2 and STAT-3 [22,23]. These results support the hypothesis that reduction of factor Xa expression in the liver may be one of the cardiprotective effects caused by ADRC administration.…”
Section: Discussionsupporting
confidence: 52%
“…Inhibition of factor Xa has been shown to reduce inflammation in a model of acute myocardial I/R injury [21]. This protective effect has been associated with phosphorylation of ERK1/2 and STAT-3 [22,23]. These results support the hypothesis that reduction of factor Xa expression in the liver may be one of the cardiprotective effects caused by ADRC administration.…”
Section: Discussionsupporting
confidence: 52%
“…In multiple preclinical models of cardiac I/R injury, APC has demonstrated significant benefits. [59][60][61][62][63] PAR1 and EPCR were required for the in vivo beneficial effects of APC in murine coronary I/R injury. 63 Despite multiple studies showing reduction of coronary I/R injury, it remains to be established how long after ischemia onset APC may be beneficial or what receptors, in addition to PAR1, mediate APC's cardioprotection.…”
Section: Wt-apc: Preclinical Studiesmentioning
confidence: 98%
“…Indeed it was shown that APC protects the heart from ischemia reperfusion (I/R) injury through PAR1 signaling. In the early inflammatory phase, APC decreases apoptosis, secretion of the pro-inflammatory cytokine IL-6 and leukocyte infiltration 142 . Activation of PAR2 also protects the heart from I/R injury by decreasing oxidative injury and increased expression and secretion of the antiinflammatory cytokine TNFα EC: PAR1 mediates vaso-relaxation, however when endothelium is damaged PAR1-mediated response shifts to vaso-constriction 153 .…”
Section: Cardio-protective Effectsmentioning
confidence: 99%